Social enjoyment with electronic photo displays: Awareness and control - Lindley, Siân; Monk, Andrew (International Journal of Human-Computer Studies, 2008)
Two experiments are reported in which groups of three friends socialised around their own photos. The photos were of two types, depicting events where all three had been present, permitting reminiscing, and events where only the photographer had been present, permitting storytelling. In Experiment 1 the seating arrangement was manipulated so that the two audience members sat either behind or around the photographer. It was hypothesised that the former would lower levels of peripheral awareness within the groups, resulting in a more formal conversation and a poorer recreational experience. In Experiment 2, control over the photos was manipulated so that either only the photographer had access to a remote control (single control) or all three group members did (distributed control). It was hypothesised that distributed control would result in less formal conversations and a better recreational experience. In both experiments the hypotheses were supported: patterns of social interaction were significantly affected by the manipulation of awareness during storytelling, and by the manipulation of control during reminiscing. Additionally, the two manipulations were found to affect ratings of enjoyment and fun, respectively. The results are interpreted in terms of a causative model of unfolding and recounted behaviour.